Longitudinal Changes in the Composition of the Penile Microbiome Are Associated With Circumcision Status, HIV and HSV-2 Status, Sexual Practices, and Female Partner Microbiome Composition - Mehta, Supriya D.; Nandi, Debarghya; Agingu, Walter; Green, Stefan J.; Otieno, Fredrick O.; Bhaumik, Dulal K.; Bailey, Robert C. (Frontiers in Cellular and Infection Microbiology, 2022)
Background: Penile microbiome composition has been associated with HSV-2 and HIV in men, and with Bacterial vaginosis (BV) and HSV-2 in female sex partners. This study sought to: (1) characterize penile microbiome composition over a one-year period, and (2) identify factors associated with penile microbiome composition over time. Methods: This prospective study of community-recruited heterosexual couples in Kenya measured penile and vaginal microbiomes via 16S ribosomal RNA gene amplicon sequencing at 4 time points over one year (1- , 6-, and 12- months after baseline). We used longitudinal mixed effects modeling to assess associated demographic, behavioral and disease factors and change in community type, meatal taxa with the highest mean relative abundance, and alpha and beta diversity measures. We estimated group-based trajectories to elucidate compositional trends. Results: Among 218 men with 740 observations, median age was 26 years, 11.6% living with HIV, and 46.1% HSV-2 seropositive. We identified 7 penile community types that varied with circumcision status, female partner vaginal microbiome community state type (CST), condom use, and penile washing. Across analytic approaches, 50-60% of men had stable penile microbiome compositions. Alpha diversity measures were lower for circumcised men and those with condom use; they were stable over time but higher if female partner had diverse CST or BV. BV was positively associated with relative abundance of numerous individual penile taxa. Decreased Bray-Curtis similarity was more common for men with HSV-2; HSV-2 was also associated with lower relative abundance Corynebacterium and Staphylococcus. Conclusions: Over a one-year period, penile microbiome composition was stable for a substantial proportion of men, and was influenced by circumcision status, sexual practices, female partner’s vaginal CST and BV status, and men’s HSV-2 status. A diverse vaginal CST is often associated with poorer health outcomes. Our results contribute towards understanding whether this framework extends to the penile microbiome, and whether diversity and the associated penile microbiome compositions influence susceptibility or resilience to poorer health outcomes in men. Focusing on understanding how these factors influence the penile microbiome may lead to therapeutic avenues for reduced HSV-2 and BV infections in men and their female sex partners.